ANALISIS EKONOMI DAN INVESTASI PERANCANGAN PLTS ATAP DI KANDANG AYAM CLOSED HOUSE UNIVERSITAS UDAYANA - Permadani, A.; Setiawan, I N.; Santiari, D. A. S. (Jurnal SPEKTRUM, 2025)
Udayana University Closed House (CH) Chicken Cage is a broiler chicken coop with a closed system equipped with a temperature and humidity control system, such as exhaust fan, cooling pad, heater, and lighting that is active for 24 hours. The necessity of the system to continue to be on, causes the operation of this system to require high electricity consumption, so the implementation of rooftop Solar Power Plants (PLTS) is considered as a solution to provide an environmentally friendly alternative energy supply in the CH Chicken Cage of Udayana University. This study was carried out with two scenarios: (1) the optimal tilt angle of 14.66° and (2) the real slope angle of the roof of 8°. Economic analysis and investment feasibility were carried out using the Net Present Value, Internal Rate of Return, Payback Period, and Profitable Index methods. The results show that scenario 2 is more feasible to develop, because the initial investment is Rp. 173,795,000 and the Payback Period is 10.64 years, which is lower than scenario 1.